MOTIVATIONAL TRAINING TO ENHANCE ENTREPRENEURIAL SUCCESS - Arifin Djakasaputra; Elizabeth Christinio; Yunia Arinda Jayanti (Transpublika Publisher, 2024)
Motivation plays an important role in the process of achieving business success. Having strong employee motivation can increase effective work commitment and ultimately lead to business success. The purpose of the activity is to help business owners have a stock of knowledge about motivation, so that business owners can increase success in entrepreneurship. The partner chosen in the community services (PKM) activity is engaged in a culinary business domiciled in Jambi. The method offered to partners is training/socialization which includes an introduction to the basic concepts of motivation, various theories of motivation, and the motivational process The results of this activity show that training on motivation in increasing entrepreneurial success is carried out by socializing to partners including an introduction to the basic concepts of motivation, various theories of motivation, and the motivational process has run smoothly. Partners were eager to receive the material presented by the PKM team. During the socialization process, partners had many discussions and questions and answers with PKM implementers. The results of the evaluation of the partners' answers to the understanding of the material were well understood. It is evident from the answers of partners who 100% can understand the material presented.